Effect of hydrophobicity on micellar binding of carminic acid - GÖKTÜRK, SİNEM (ELSEVIER SCIENCE SA, 2005)
The effect of hydrophobicity on micellar binding of carminic acid (CA), an anionic dye, with various cationic surfactants; dodecyltrimethylammonium bromide (C(12)TAB), tetradecyltrimethylammonium bromide (C(14)TAB), cetyltrimethylammonium bromide (C(16)TAB) cetylpyridinium bromide (C16PBr) and cetylpyridinium chloride (C16PC) has been studied spectrophotometrically in submicellar and micellar concentration range. Going from aqueous solution to the more hydrophobic micellar environment the maximum absorbance of CA shifted a higher wavelength in its absorption maxima. The binding constant (K-c) values of CA to cationic micelles were calculated by means of Benesi-Hildebrand Equation and the binding of CA followed the order as: C16PB > C16PC > C(16)TAB > C(14)TAB > C(12)TAB The K-c values and the absorption maxima of CA in the presence of micelles showed that hydrophobic interaction plays a major role in binding process of CA to cationic micelles. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: carminic acid; binding constant; hydrophobic interaction; micelles; cationic surfactants; AMPHIPHILIC HEMICYANINE DYES; CATIONIC SURFACTANT INTERACTIONS; ANIONIC SURFACTANT; COMPLEX-FORMATION; FLUORESCENCE; BROMIDE; SOLUBILIZATION; SPECTROSCOPY; ASSOCIATION; PINACYANOL